The metabolic determinants of the response to ketone bodies in SH-SY5Y neuroblastoma cells - ALHERZ, MOHAMMAD (Trinity College Dublin. School of Medicine. Discipline of Anatomy, 2020)
Neuroblastoma (NB) is a childhood malignancy of the sympathetic nervous system. Its mutual neoplastic and neurodevelopmental underpinnings are characterised by an excessive glucose demand as a hallmark of a high proliferative capacity. This metabolic phenotype is reported as a barrier to ketone utilization and an avenue for dietary therapies designed to alter substrate availability and starve cells from their preferred biosynthetic requirements. However, the effects of ketones in both cancer and foetal development are equally diverse and poorly understood. In pursuit of a transferrable in vitro model of glucose deprivation, ketosis and the potentially confounding interactions with other fuel substrates, we investigate how the primary ketone body Beta-hydroxybutyrate (BOHB) affects the growth, survival and morphology of undifferentiated SH-SY5Y NB cells in the presence or absence of glucose, pyruvate and glutamine from the culture medium. We demonstrate that while glucose deprivation diminishes the growth and viability of cells, they can continue to survive and proliferate, and are initially unaffected by various concentrations of BOHB. Subsequent alteration of the culture conditions reveals that a growth-promoting effect of BOHB is masked by the concentration of glucose and the presence of pyruvate, drawing attention to substrate availability as a determinant of the differential responses reported in models of neoplasia and development. Finally, based on the speculative mechanisms of this differential response, we present findings supporting a rationale for combining ketosis with metformin as a potential anticancer therapy. The implications include a preliminary framework for understanding the interfering mechanisms of other substrates in the metabolism of ketones in terms of reversible enzymatic pathways, the overall energy balance, and the potential for competition at the transporter level. With this understanding of an adjustable response to ketones, variations in how different cells react according to their intrinsic characteristics may allow selective pharmacological inhibition of NB ketone metabolism using metformin for instance, while allowing healthy cells to continue utilising this alternative fuel. In conclusion, the modifiable environment of the cells is a key determinant of their response to BOHB in vitro.
APPROVED
Keywords: Cancer; Neuroblastoma; Metformin; Ketogenic Diet; Warburg Effect; Metabolism; Proliferation; Morphology; Beta-Hydroxybutyrate; Cell Culture; Neurodevelopment; Pyruvate; Lactate; Glucose; Glutamine